(untitled) (Third Sector Social Economic Review, 2026)
This study examines the managerial tunnel effect in digitalizing organizations within a conceptual framework and proposes an original model that integrates concepts often addressed in a fragmented manner in the literature. Organizational myopia, strategic short-termism, narrow vision, managerial blindness, collective blindness, silo syndrome, analytical maturity myopia, and future myopia are systematically discussed across cognitive, structural, cultural, and technological dimensions. The proposed conceptual model demonstrates that the managerial tunnel effect does not arise solely from individual cognitive limitations but also from the interaction of organizational norms, structural disconnections, and performance pressures generated by digitalization. The model highlights negative outcomes such as the loss of strategic diversity, weakened organizational learning, and sustainability risks, while also emphasizing intervention areas including organizational learning, strategic foresight, cultural transformation, and the institutionalization of long-term performance indicators. In this way, the study addresses the conceptual fragmentation in the literature and provides a holistic theoretical framework for understanding the managerial tunnel effect. Furthermore, it explains new forms of blindness emerging in the context of digitalization and develops solution-oriented recommendations for both academia and practice.